Predicting the presence and titre of rabies virus‐neutralizing antibodies from low‐volume serum samples in low‐containment facilities. Issue 3 (23rd September 2020) - Meza, Diana K.; Broos, Alice; Becker, Daniel J.; Behdenna, Abdelkader; Willett, Brian J.; Viana, Mafalda; Streicker, Daniel G.
Abstract: Serology is a core component of the surveillance and management of viral zoonoses. Virus neutralization tests are a gold standard serological diagnostic, but requirements for large volumes of serum and high biosafety containment can limit widespread use. Here, focusing on Rabies lyssavirus, a globally important zoonosis, we developed a pseudotype micro‐neutralization rapid fluorescent focus inhibition test (pmRFFIT) that overcomes these limitations. Specifically, we adapted an existing micro‐neutralization test to use a green fluorescent protein‐tagged murine leukaemia virus pseudotype in lieu of pathogenic rabies virus, reducing the need for specialized reagents for antigen detection and enabling use in low‐containment laboratories. We further used statistical models to generate rapid, quantitative predictions of the probability and titre of rabies virus‐neutralizing antibodies from microscopic imaging of neutralization outcomes. Using 47 serum samples from domestic dogs with neutralizing antibody titres estimated using the fluorescent antibody virus neutralization test (FAVN), pmRFFIT showed moderate sensitivity (78.79%) and high specificity (84.62%). Despite small conflicts, titre predictions were correlated across tests repeated on different dates both for dog samples ( r = 0.93) and in a second data set of sera from wild common vampire bats ( r = 0.72, N = 41), indicating repeatability. Our test uses a starting volume of 3.5 µl of serum, estimates titres from a single dilution of serum rather than requiring multiple dilutions and end point titration, and may be adapted to target neutralizing antibodies against alternative lyssavirus species. The pmRFFIT enables high‐throughput detection of rabies virus‐neutralizing antibodies in low‐biocontainment settings and is suited to studies in wild or captive animals where large serum volumes cannot be obtained.